Spatial transcription of CYP1A in fish liver - Olsvik, Pål A.; Lie, Kai K.; Sæle, Øystein; Sanden, Monica (BMC Physiology, 2007)
Background: The aim of this work was to study how evenly detoxifying genes are transcribed spatially in liver tissue of fish. Ten Atlantic salmon Salmo salar were intraperitoneally injected with 50 mg/kg of the strong CYP1A inducer β-naphthoflavone and liver tissue harvested seven days later. The liver from 10 control and 10 exposed fish were split into eight sections, RNA extracted and three reference (β-actin, elongation factor 1AB (EF1AB)) and two detoxifying genes (CYP1A and GST) quantified with real-time RT-PCR. The cellular localization of the EF1AB and CYP1A mRNA in the liver of control and β-naphthoflavone treated fish was then determined by in situ hybridization (ISH) using EF1AB and CYP1A biotinylated oligonucleotide probes. Results: The study shows that genes encoding phase I and phase II conjugating enzymes are unevenly transcribed in different parts of the liver of Atlantic salmon seven days after a single-dose of β-naphthoflavone exposure. Transcription of CYP1A and GST was higher in the middle section of the liver compared to the distal and proximal parts of the organ. The ISH data suggest that CYP1A transcription happens mainly in hepatocyte cells in the liver, and that hepatocytes in the vicinity of blood vessels respond stronger to β-naphthoflavone than cells further away from the blood supply. Conclusion: Overall, the qRT-PCR and ISH results reported here suggest that gene expression analysis should be performed on as pure cell populations as possible. If bulk tissue samples are to be used, one should always check how evenly the target genes are expressed in tissue sections and organs in every study.